Interaction between aerobic/anaerobic loading and biomechanical performance in freestyle swimming - Keskinen, K. L.; Komi, P. V. (Swimming Science V, 1988)
The mean velocity of freestyle swimming (V) is equal to the product of the stroke rate (SR) and the stroke length (SL). SR refers to one complete cycle of one arm in a given unit of time. The duration of a stroke cycle depends on the angular velocity of rotational movement of the arm around the shoulder joint and on the distance that the most distal part of the upper extremity travels through the water and the air during stroking. SL is the distance that the swimmer moves forward during one complete stroke cycle of one arm. It depends on the horizontal components of drag and lift forces on segments of a swimmer and therefore on the swimmer's muscular power output (Grimston & Hay, 1986; Hay, 1978; Miller, 1975). In general, SR and SL are negatively related to each other, and the combination of these two variables is highly individualized. Although the interdependence of SR and SL is very high, several factors may influence their interrelationships. Among them are anthropometric characteristics, which have been shown to influence SR and more importantly SL {Oarys, Jiskoot, Rijken, & Brouwer, 1974; DeGaray, Levine, & Carter, 1974; Grimston & Hay, 1986; Reischle, 1978). The swimming velocity may also have different reflections on SR and SL depending on the individual's performance capacity in water and swimming skill. The increase in V has been found to be more strongly related to an increase in SR than to a decrease in SL, and SL demonstrates considerable intra- and interindividual variability. However, a hypothesis has been proposed that SR cannot be increased beyond the optimal level without a loss in V (Craig & Pendergast, 1979; East, 1970). Furthermore, the swimmers with different swimming performances have much greater variability in SL than in SR in competitive swimming (Craig & Pendergast, 1979; Craig, Skehan, Pawelczyk, & Boomer, 1985; East, 1970; Hay & Guimares, 1983; Letzelter & Freitag, 1982). These observations have led to the assumption that the complex interrelationship among SR, SL, and V may reflect individual swimming efficiency as well as overall metabolism (Costill et al., 1985). The present study was therefore designed to evaluate V of freestyle swimming utilizing the SR and SL in three different intensity levels in aerobic/ anaerobic loading situations.